2016
DOI: 10.1186/s40104-016-0120-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical changes of rapeseed meal proteins during toasting and their effects on in vitro digestibility

Abstract: BackgroundToasting during the production of rapeseed meal (RSM) decreases ileal crude protein (CP) and amino acid (AA) digestibility. The mechanisms that determine the decrease in digestibility have not been fully elucidated. A high protein quality, low-denatured, RSM was produced and toasted up to 120 min, with samples taken every 20 min. The aim of this study was to characterize secondary structure and chemical changes of proteins and glucosinolates occurring during toasting of RSM and the effects on its in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Thus, these results clearly demonstrated that extreme temperatures used during the toasting step did not change the protein content of the meals. Moreover, this recalcitrant aspect of proteins has already been observed in other studies where it was demonstrated that desolventization/toasting steps applied on RSM did not affect its protein content (Mosenthin et al, 2016;Salazar-Villanea et al, 2016).…”
Section: Proteins Simple Phenolic Compounds and Glucosinolate Contentssupporting
confidence: 71%
See 2 more Smart Citations
“…Thus, these results clearly demonstrated that extreme temperatures used during the toasting step did not change the protein content of the meals. Moreover, this recalcitrant aspect of proteins has already been observed in other studies where it was demonstrated that desolventization/toasting steps applied on RSM did not affect its protein content (Mosenthin et al, 2016;Salazar-Villanea et al, 2016).…”
Section: Proteins Simple Phenolic Compounds and Glucosinolate Contentssupporting
confidence: 71%
“…1). This can be explained by the possible modification of techno-functional properties of proteins due to the harsh implemented conditions (Salazar-Villanea et al, 2016). Indeed, according to Salazar-Villanea et al 2017, reduction of protein solubility in RSM is linked to physical (aggregation phenomenon) and chemical (Maillard reactions) modifications of their structures, which lead to a decrease of their digestibility and solubility.…”
Section: Proteins Simple Phenolic Compounds and Glucosinolate Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the present study was to determine the effects of toasting time during the production process of RSM on the kinetics of hydrolysis of proteins present in the complete material, and in its soluble and insoluble fractions, and on the resulting molecular size distribution of the peptides after hydrolysis. Previous results from our research group indicate that there is a highly significant positive correlation between nitrogen solubility and the rate of protein hydrolysis [3]. Therefore, we hypothesize that the rate of hydrolysis will be higher for the soluble protein fraction compared with the insoluble protein fraction, but that the rates at different toasting times will not vary within the soluble and the insoluble protein fractions.…”
Section: Introductionmentioning
confidence: 75%
“…The production of defatted 00-rapeseed meal (RSM) involves toasting for the removal of remnant solvent after oil extraction, the inactivation of myrosinase and the degradation of glucosinolates [1][2][3], the main antinutritional factors of RSM for monogastric animals. Increasing the toasting time decreases protein solubility [1,3] and the contents of lysine [1,3,4] and reactive lysine [2,3] of the resulting RSM. Reactive lysine can be considered as the proteinbound lysine with a free ε-amino group [5].…”
Section: Introductionmentioning
confidence: 99%